Pengaruh Lingkungan Kerja, Disiplin Kerja, Religiusitas dan Kompensasi Terhadap Kinerja Pegawai Badan Amil Zakat Nasional Provinsi Kalimantan Timur - Safu'an Mahfud Effendi; Moh. Mahrus; Muhammad Hasbi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Abstract Quality human resources are a factor in supporting the company's success in achieving its goals. There need to be supporting factors, namely the work environment to make employees feel comfortable and safe at work, work discipline to provide a sense of responsibility to employees at work, religiosity to create employees who are obedient to the teachings of their religion, then compensation to provide employee welfare. This study aims to determine whether the work environment, work discipline, religiosity and compensation affect the performance of the employees of the National Amil Zakat Agency of East Kalimantan Province. The type of research used is an associative research method with a quantitative collection strategy. This study uses primary data from observations, questionnaires, documentation, and interviews. The total population in this study was 19 respondents with a sampling technique, namely Saturated Sampling so that the total number of the population was used as the research sample. The analytical technique used in this study is to test the validity of the data, namely the validity and reliability test, then the classical assumption test, multiple linear regression test and hypothesis testing consisting of t-test and F-test and the coefficient of determination (R2) with SPSS 21 data processing. The results of the study, it was found that partially the work environment variable had a significant effect on employee performance with a significant value of 0,003 < 0,05, besides the work discipline variable had a significant effect on employee performance with significant value 0,049 < 0,05 and the religiosity variable had no significant effect on employee performance with significant value 0,0331 > 0,05 and the compensation variable did not significantly affect employee performance with significant value 0,700 > 0,05. then the results of the test calculation simultaneously obtained that the variables of work environment, work discipline, religiosity and compensation have a simultaneous effect on the performance of the employees of the National Amil Zakat Agency of East Kalimantan Provincewith significant value 0,000 < 0,05 . And the results of the coefficient of determination showed that the variables of work environment, work discipline, religiosity and compensation on employee performance in this study amounted to 71.0% while the remaining were influenced by other variables. Keywords: Work Environment, Work Discipline, Religiosity, Compensation, Performance